Bernhard Varenius: (1622 - 1650) - Schuchard, Margret (BRILL, 2014)
This fresh portrait of Varenius presents a young German scholar, whose books on Japan (1649), the first one from a European perspective, and on General Geography (1650) were written and published in Amsterdam and led to establishing geography as a science.
Description based on publisher supplied metadata and other sources
Keywords: Aufsatzsammlung; Konferenzschrift; Geschichte; Geografie; Varenius, Bernhardus